2021
DOI: 10.4081/dr.2021.9143
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Mediterranean diet in acne pathogenesis and the correlation with insulin-like growth factor-1 serum levels: implications and results

Abstract: Acne is a chronic inflammatory disease of the pilosebaceous unit and its etiology is complex and multifactorial. The role of the diet in its pathogenesis is still debated. The purpose of this study was to assess the association between MD and IGF-1 in acne patients and, as secondary objective, the role of systemic treatment on IGF-1 serum levels, in accordance to the patients’ diet. This study included 35 patients aged 14-30 years affected by acne and treated in line with the EDF guidelines. Patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Research on the impact of adherence to a whole dietary pattern, such as the MD, on acne is scarce. Only a few studies have suggested a protective effect of adherence to the MD on acne [ 39 42 ]. However, these studies were limited to populations residing in southern European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the impact of adherence to a whole dietary pattern, such as the MD, on acne is scarce. Only a few studies have suggested a protective effect of adherence to the MD on acne [ 39 42 ]. However, these studies were limited to populations residing in southern European countries.…”
Section: Introductionmentioning
confidence: 99%